Education policy, space, and the city : markets and the (in)visibility of race - Gulson, Kalervo N. (New York : Routledge, 2011)
With urbanization as one of the central concerns for the future, relationships between the city, educational policy, and social and educational inequality deserve sustained examination. This book offers contribution to these areas of study. It examines the relationships between educational policy, space and place
Includes bibliographical references and index.
Keywords: Education, Urban -- Case studies -- Government policy; Race discrimination -- Case studies; City children -- Case studies. -- Education -- Government policy; Urban geology -- Case studies. -- Government policy